Metal‐Organic Frameworks: 2D Metal–Organic Framework Nanosheets with Time‐Dependent and Multilevel Memristive Switching (Adv. Funct. Mater. 3/2019). (15th January 2019) - Ding, Guanglong; Wang, Yaxin; Zhang, Guixian; Zhou, Kui; Zeng, Kelin; Li, Zongxiao; Zhou, Ye; Zhang, Chen; Chen, Xiaoli; Han, Su‐Ting
Abstract : In article number1806637, Ye Zhou, Su‐Ting Han, and co‐workers demonstrate a 2D metal‐organic framework nanosheet based memory device with a typical bipolar switching behaviour, superior retention, and high reliability. The devices show excellent multilevel information storage performance, and the percolated conducting paths model has been verified by the Weibull distribution.